PENGARUH DISIPLIN KERJA PEGAWAI TERHADAP PELAYANAN DI KANTOR SATUAN POLISI PAMONG PRAJA SAMARINDA - ., Fatimah (PREDIKSI, 2012)
The aimed ofthis research is to find out the influence significantly work discipline to service at Samarinda Police Union Pamong Praja Office.Hypothesis which researcher is have proposed in this research is contents : there is positive influence work discipline to service at Samarinda Police Union Pamong Praja Office.Sampling of this research is a few of employee at Samarinda Police Union Pamong Praja Office amount 30 persons. The used instrument to find out the data in this research is the questionnaire, that used to know the work discipline and service Samarinda Police Union Pamong Praja Office. The data analysis done with product moment correlation and simple regression linier analysis.The result of analysis calculation product moment correlation between employee work discipline variabel (X) with employee service (Y) at Samarinda Police Union Pamong Praja Office show correlation coefficient amount r = 0,645. This case mean there is positive correlation between work discipline with employee service at Samarinda Police Union Pamong Praja Office. Whereas based on interpretation criteria correlation coefficient amount 0,645 be in strong connection level. The result of regression linier analysis also show determinant coefficient amount r2 = 0,416. This case mean hypothesis which proposed in this research is accepted. Based on count get the regression similarity below : Y = 8,103 + 0,667 X. With this can be concluded that employee work discipline has positive and significant influent to employee service at Samarinda Police Union Pamong Praja Office are 41,60%.